﻿Three new deep-sea species of Marphysa (Annelida, Eunicida, Eunicidae) from Papua New Guinea (Bismarck and Solomon seas) - Nicolas Lavesque; Guillemine Daffe; Christopher Glasby; Stéphane Hourdez; Pat Hutchings (ZooKeys, 2022)
Three new species of Marphysa Quatrefages, 1866, Marphysa banana sp. nov., Marphysa papuaensis sp. nov., and Marphysa zanolae sp. nov. are described from deep-sea sunken vegetation off Papua New Guinea, using both morphology and molecular data (for two species). With the presence of compound spinigers only and the branchiae present over many chaetigers, Marphysa banana sp. nov. belongs to the group B2. This species is characterised by the presence of eyes, the presence of branchiae starting from chaetiger 20, and by the presence of three types of pectinate chaetae and bidentate subacicular hooks starting from chaetigers 13–52. With the presence of compound falcigers only and the branchiae restricted to a short anterior region, Marphysa papuaensis sp. nov. belongs to the group C1. This species has a bilobed prostomium but no eyes, has branchiae from chaetigers 7 to 14–16 with up to 16 filaments. Marphysa papuaensis sp. nov. is also characterised by the presence of bidentate subacicular hooks from chaetiger 20 and by a single type of pectinate chaetae. Finally, Marphysa zanolae sp. nov. belongs to the group C2, with the presence of compound falcigers only and the branchiae present over many chaetigers. This species is characterised by the absence of eyes, by the presence of branchiae with a single long filament starting from chaetiger 31, by unidentate subacicular hooks starting from chaetiger 28 and finally by one type of pectinate chaetae with very long outer teeth.